CONTEXTUAL AND PHONOLOGICAL APPROACHES IN EARLY READING INSTRUCTION IN ELEMENTARY SCHOOLS - Nurul Fatonah; Vismaia S Damaianti; Ernawulan Syaodih (Jurnal Cakrawala Pendas, 2026)
Early reading is a fundamental skill that supports students’ cognitive and academic development in elementary education. However, many students still experience difficulties in recognizing letters, associating sounds with symbols, and understanding simple texts. These challenges indicate that early reading instruction has not optimally integrated phonological and contextual aspects of learning. This study aimed to develop a learning approach that integrates contextual and phonological aspects in early reading instruction. The research employed an Educational Design Research approach consisting of analysis, design, and evaluation stages. The participants included expert validators, elementary school teachers, and first-grade students. Data were collected through validation sheets, observation, questionnaires, and early reading tests. The results show that the developed learning approach is valid and feasible to be implemented in early reading instruction. The validation results indicate a high level of validity, and the learning process becomes more meaningful through the integration of contextual experiences and sound-symbol recognition. Students demonstrate better engagement and participation during the learning process. In conclusion, the integration of contextual and phonological approaches is appropriate for early reading instruction and has the potential to improve students’ early reading skills in elementary schools.